Clinical Utility of the Combined Positive Score for Programmed Death Ligand-1 Expression and the Approval of Pembrolizumab for Treatment of Gastric Cancer. - Kulangara, Karina; Zhang, Nancy; Corigliano, Ellie; Guerrero, Lindsay; Waldroup, Stephanie; Jaiswal, Dipeshkumar; Jansson, Malinka; Shah, Supriya; Hanks, Debra; Jiangdian Wang; Lunceford, Jared; Savage, Mary J.; et al. (Archives of Pathology & Laboratory Medicine, 2019)
Context.--Regulatory approval of pembrolizumab for treatment of gastric and gastroesophageal junction (G/GEJ) adenocarcinoma required a reproducible scoring method for use of programmed death ligand-1 (PD-L1) protein expression as a companion diagnostic to identify likely responders to therapy. Objective.--To develop an immunohistochemical scoring algorithm that includes PD-L1 expression for tumor and immune cells, that is, the combined positive score. Design.--Four previously treated tumor types in the KEYNOTE-012 and KEYNOTE-028 studies were analyzed descriptively with a version of the PD-L1 immunohistochemical 22C3 pharmDx assay labeled for investigational use only to determine the relative importance of PD-L1 expression in tumor versus immune cells as a biomarker for pembrolizumab response. A combined positive score was developed as a novel scoring method and was compared with the tumor proportion score in cohort 1 from the KEYNOTE-059 study (G/GEJ cancer). External reproducibility was assessed. Results.--Per combined positive score cutoff of 1 or more, the prevalence of PD-L1 expression in patients with G/GEJ cancer was 57.6% (148 of 257 patients), with reasonable enrichment of responses (odds ratio, 2.8). Per tumor proportion score cutoff of 1% or more, prevalence was 12.5% (32 of 257 patients), with minimal enrichment (odds ratio, 1.4). External reproducibility assessments demonstrated interpathologist overall agreement of 96.6% (591 of 612; 95% CI, 94.0%--98.7%) and intrapathologist overall agreement of 97.2% (595 of 612; 95% CI, 95.3%--98.9%). Conclusions.--Combined positive score is a robust, reproducible PD-L1 scoring method that predicts response to pembrolizumab in patients with G/GEJ cancer. This novel scoring method supported US Food and Drug Administration approval of pembrolizumab as third-line therapy for G/GEJ cancer and has facilitated investigation in other indications.